Sedimentological re-interpretation of the early cretaceous oil reservoir in the Northern Bredasdorp Basin, offshore South Africa - Asiashu, Mudau (University of the Western Cape, 2016)
>Magister Scientiae - MSc === This study was aimed at determining the sedimentary environment, its evolution and facies areal distribution of the Upper Shallow Marine (USM, Late Valanginian). The study was conducted in wells E-S1, F-AH4 and E-W1 in the Bredasdorp basin between E-M and F-AH fields, located in a basinwards transect roughly transverse to the palaeocoast. The wells were studied by logging all the cores in detail between the chosen intervals, followed by facies analysis. Each core log was tied with its respective gamma ray and resistivity well logs. The logs were then correlated based on their log signatures, trends and facies interpretation. The Gamma ray logs show a fining-upwards and coarsening-upwards trend (“hour-glass shape”) in E-S1 and F-AH4 while in E-W1 it shows more accommodation space. These trends are believed to have been influenced by relative sea level changes, such as transgression and regression. Facies analysis identified seven facies in the study area: Facies A, B, C, D, E, F and G. Facies A, B and C were interpreted as fair-weather and storm deposits of the offshore-transition zone, shoreface and foreshore respectively. Facies D was considered as lagoonal mud deposits, while Facies E and F were interpreted as tidal channel and tidal bar deposits respectively. Finally Facies G was considered as fluvial channel deposits. The facies inferred that the sedimentary environment of the study area is a wave-dominated estuary or an Island-bar lagoon system. This led to the production of a conceptual model showing the possible locations for the three wells in the Island bar-lagoon system. The conceptual model inferred the previous findings from PGS (1999) report, that the Upper Shallow Marine beds were deposited in a tidal/estuarine to shoreface setting. This model also supports the findings of Magobiyane (2014), which proposed a wave-dominated estuary for the Upper Shallow Marine reservoir between E-M and F-AH fields, located west of the study area.